Active learning of Physics during the practice of the Simple Pendulum through Simulation - Calle Chumo, Rafael Norberto (2022)
The purpose of this article was to analyze the performance of two methodologies to improve the teaching of Physics, through a comparison between traditional teaching and active teaching, during the practice of the Simple Pendulum in high school students. An exploratory level research methodology with a quantitative approach was used. The study presented guidelines and instructions to improve the teaching of the Simple Pendulum assisted by the PODS cycle; Prediction, Observation, Discussion and Synthesis. For this, the normalized Hake gain was determined against the two training scenarios; traditional (control groups) versus non traditional (experimental groups). As a result, both methodologies were compared and two rejection indicators were presented: probability less than 0.05 and an F factor greater than the critical factor of F. Next, a post-hoc analysis supported by the Tukey test verified the groups with greater differences between the mean grades. At the end, it was verified that the active methodology of the PODS cycle generated greater learning gain for the experimental groups since their distribution widths were smaller than those reported with traditional teaching.